Alkaloidal Extracts from Avicennia africana P. Beauv. (Avicenniaceae) Leaf: An Antiplasmodial, Antioxidant, and Erythrocyte Viable - Ahmed, M.A.; Ameyaw, E.O.; Zoiku, F.K.; et al. (Advances in Pharmacological and Pharmaceutical Sciences, 2024)
Background. Te emergence of drug-resistant parasites impedes disease management and eradication eforts. Hence, a rein vigorated attempt to search for potent lead compounds in the mangroves is imperative. Aim. Tis study evaluates in vitro antiplasmodial activity, antioxidant properties, and cytotoxicity of A. africana leaf alkaloidal extracts. Methods. Te A. africana leaves were macerated with 70% ethanol to obtain a total crude extract. Dichloromethane and chloroform-isopropanol (3 :1, v/v) were used to extract the crude alkaloids and quaternary alkaloids from the total crude. Te antiplasmodial activities of the alkaloidal extracts were performed against 3D7 P. falciparum chloroquine-sensitive clone via the SYBR Green I fuorescence assay with artesunate serving as the reference drug. Te alkaloidal extracts were further evaluated for antioxidant properties via the total antioxidant capacity (TAC), the total glutathione concentration (GSH), the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, and the ferric-reducing antioxidant power (FRAP) methods. Te cytotoxic activity of the alkaloidal extracts was tested on erythrocytes using a 3-(4,5-dimethylthiazol-2-yl)-5-diphenyltetrazolium bromide-MTTassay with little modifcation. Te phytocompounds in the alkaloidal extracts were identifed via gas chromatography-mass spectrometry (GC-MS) techniques. Results. Te total crude extract showed good antiplasmodial activity (IC50 = 11.890 µg/mL). Te crude and quaternary alkaloidal extracts demonstrated promising antiplasmodial efects with IC50 values of 6.217 and 6.285 µg/mL, respectively. Te total crude and alkaloidal extracts showed good antioxidant properties with negligible cytotoxicity on erythrocytes with good selectivity indices. Te GC-MS spectral analysis of crude alkaloidal extracts gave indole and isoquinoline alkaloids and several other compounds. Dexrazoxane was found to be the main compound predicted, with an 86% peak area in the quaternary alkaloidal extract. Conclusion. Te crude and quaternary alkaloidal extracts exhibited antiplasmodial activities and ability to inhibit oxidative stress with negligible toxicity on erythrocytes. Tis may be good characteristics to avoid oxidative stress related to Plasmodium infection in the treatment of malaria.
Research Article
Keywords: vitro antiplasmodial activity; antioxidant properties; A. africana leaf alkaloidal